2014
DOI: 10.3748/wjg.v20.i47.18031
|View full text |Cite
|
Sign up to set email alerts
|

Role of protective stoma in low anterior resection for rectal cancer: A meta-analysis

Abstract: AIM:To provide a comprehensive evaluation of the role of a protective stoma in low anterior resection (LAR) for rectal cancer. METHODS:The PubMed, EMBASE, and MEDLINE databases were searched for studies and relevant literature published between 2007 and 2014 regarding the construction of a protective stoma during LAR. A pooled risk ratio (RR) with 95% confidence intervals (CIs) was used to assess the outcomes of the studies, including the rate of postoperative anastomotic leakage and reoperations related to le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
1
12

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 41 publications
3
56
1
12
Order By: Relevance
“…One of the most feared complications after colorectal surgery is anastomotic leakage, with a reported incidence of between 1% and 19% . A diverting ileostomy has been shown to reduce symptomatic anastomotic leakage, but it still remains a serious complication with extensive consequences .…”
Section: Introductionmentioning
confidence: 99%
“…One of the most feared complications after colorectal surgery is anastomotic leakage, with a reported incidence of between 1% and 19% . A diverting ileostomy has been shown to reduce symptomatic anastomotic leakage, but it still remains a serious complication with extensive consequences .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies in the past have found that the rate of anastomotic leakage was not reduced by the construction of defunctioning proximal stoma [11, 13, and 18]. However, couple of recent meta-analyses have shown that defunctioning proximal stoma significantly reduces the incidence as well as the consequences of the anastomotic leakage [19,20]. In this study, rates of anastomotic leakage were higher when defunctioning proximal stoma was not constructed (14.9 % vs 6.2 %) though it did not reach statistical significance (p = 0.068).…”
Section: Discussionmentioning
confidence: 99%
“…Ряд авторов считает, что превентивные стомы «защищают» первичный анастомоз и предотвращают его несостоятельность [13,14]. В то же время большин-ство исследований убедительно свидетельствуют о том, что превентивные стомы не снижают частоту несосто-ятельности первичных анастомозов, но уменьшают ее проявления, что снижает частоту осложнений, требу-ющих оперативного лечения [2,15,16].…”
Section: отдел кишкиunclassified
“…В настоящее время их формируют при низких и ультранизких резекциях прямой кишки с тотальной мезоректумэктомией. Однако зачастую хирург при принятии решения о формировании пре-вентивной стомы руководствуется собственным опы-том и тактиками, принятыми в клинике [2,3,9,14].…”
Section: отдел кишкиunclassified
See 1 more Smart Citation